ANALISIS PENGARUH KEPUASAN DAN KEPERCAYAAN MAHASISWA TERHADAP JURUSAN EKONOMI SYARIAH DENGAN KEINGINAN UNTUK MELAKUKAN WORD OF MOUTH COMMUNICATION - Asnawi, Haris Faulidi; Faridah, Rohana; Khaliq, Restu (At-Taradhi, 2015)
This study aims to determine the effect of studentsâ satisfaction with the services of the Department of Islamic Economics toward students trust to the Department of Islamic Economics Faculty of Sharia and Islamic Economics at IAIN Antasari Banjarmasin, and the inï¬ uence of the students trust to theservice of the Department of Islamic Economics with the desire of students to do word of mouth communication, as well as the inï¬uence of studentsâ satisfaction for services to the Department of Islamic Economics toward the desire to do word of mouth communication through students trust on the Department of Economic Syariah. The Method that is used in this research is quantitative method by using path analysis. Based on the research ï¬ndings and data analysis, it can be said that satisfaction with the services the Department of Economics student of Islamic belief of the student has signiï¬cant effect and there is also insigniï¬ cant.Students trust to service of the Department of Islamic Economics with a desire to do word of mouth communication has a signiï¬cant inï¬uence. Students Satisfaction to do word of mouth communication has no signiï¬ cant effect on all aspects.